Menguji Dasar Sosiologis Sebuah Produk Hukum(Analisis Sosiologi Hukum terhadap Perpres No. 20 Tahun 2018) - Umar Sholahudin (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2019)
A good and functional legislation in the community, including the Perpres, is not only required to have a strong philosophical and juridical basis, but also sociological considerations. This article will examine the sociological basis of Peraturan Presiden No. 20 of 2018 concerning the Use of Foreign Workers in Indonesia. The issuance of the Presidential Regulation needs to be looked at and critics together whether Peraturan Presiden No. 20 of 2018 has taken into account the sociological aspects, the current dynamics and adequate future projections? This consideration needs to be done to ensure that the Perpres has a parallel and adequate basis for philosophical, juridical, and sociological visibility. This sociological consideration and basic test is important, to ensure that a legal product will be implemented effectively or not? This study uses a descriptive-qualitative method using the Legal Sociology approach. The focus studied is a legal product, namely the Peraturan Presiden No. 20 of 2018. The data used is Peraturan Presiden 20 of 2018, Central Bureau of Statistics (BPS), literature review, mass media information and other sources related to support. As a result, the issuance of Perpes No. 20 of 2018, shows that besides its weak philosophical and juridical basis, it is also weak sociologically. The employment policy outlined in the Presidential Regulation clearly neglects the sociological conditions of the Indonesian people, especially Indonesian workers A good and functional legislation in the community, including the Perpres, is not only required to have a strong philosophical and juridical basis, but also sociological considerations. This article will examine the sociological basis of Peraturan Presiden No. 20 of 2018 concerning the Use of Foreign Workers in Indonesia. The issuance of the Presidential Regulation needs to be looked at and critics together whether Peraturan Presiden No. 20 of 2018 has taken into account the sociological aspects, the current dynamics and adequate future projections? This consideration needs to be done to ensure that the Perpres has a parallel and adequate basis for philosophical, juridical, and sociological visibility. This sociological consideration and basic test is important, to ensure that a legal product will be implemented effectively or not? This study uses a descriptive-qualitative method using the Legal Sociology approach. The focus studied is a legal product, namely the Peraturan Presiden No. 20 of 2018. The data used is Peraturan Presiden 20 of 2018, Central Bureau of Statistics (BPS), literature review, mass media information and other sources related to support. As a result, the issuance of Perpes No. 20 of 2018, shows that besides its weak philosophical and juridical basis, it is also weak sociologically. The employment policy outlined in the Presidential Regulation clearly neglects the sociological conditions of the Indonesian people, especially Indonesian workers